Modern architecture : a critical history - Frampton, Kenneth (World of Art, 1997)
This acclaimed survey of 20th-century architecture and its origins has become a classic since it first appeared in 1980. Now revised, enlarged and expanded, Kenneth Frampton brings the story up to date and adds an entirely new concluding chapter that focuses on four countries where individual talent and enlightened patronage have combined to produce a comprehensive and convincing architectural culture: Finland, France, Spain and Japan.